2002
DOI: 10.1046/j.1524-475x.2002.10509.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferating effect of latent transforming growth factor‐β1 is cell membrane dependent

Abstract: The mechanism of in vivo activation of transforming growth factor-beta1 (TGF-beta1), which is critical to its role in many physiological and pathological conditions, is not fully understood. To explore the mechanism by which dermal fibroblasts respond to latent TGF-beta1 directly, the efficacy of either latent TGF-beta1 (LTGF-beta1) alone or LTGF-beta1 plus cell membranes isolated from fibroblasts, mink lung, and one skin-related (Sk23) and two skin-unrelated (U251 and D54MG) transformed cell lines was examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Each TGF‐β isoform is synthesized as a latent complex consisting of a 25‐kDa dimeric mature protein and the dimeric N‐terminal precursor peptide known as the latency associated peptide. The latent form of TGF‐β is activated through interactions with the M6P/IGF‐IIR 8,15 . In our coculture system, we have demonstrated that coculture of KKs and KFs also results in increased expression of M6P/IGF‐IIR in fibroblasts correlating with the increased levels of active TGF‐β in the conditioned medium.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Each TGF‐β isoform is synthesized as a latent complex consisting of a 25‐kDa dimeric mature protein and the dimeric N‐terminal precursor peptide known as the latency associated peptide. The latent form of TGF‐β is activated through interactions with the M6P/IGF‐IIR 8,15 . In our coculture system, we have demonstrated that coculture of KKs and KFs also results in increased expression of M6P/IGF‐IIR in fibroblasts correlating with the increased levels of active TGF‐β in the conditioned medium.…”
Section: Discussionmentioning
confidence: 67%
“…Mannose‐6‐phosphate/IGF insulin‐like growth factor II receptor (M6P/IGF‐IIR) plays an important role in activation of latent TGF‐β 8,15 . We demonstrate that KFs expressed four times M6P/IGF‐IIR than NFs without the presence of keratinocytes.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…While this search for TRPC channels involved a number of widely used cell lines and patient biopsies we chose one cell line in particular, D54MG, for our biophysical studies. D54MG glioma cells are derived from a high‐grade (WHO grade IV) glioma and have been widely used and extensively described in the literature (Ghahary et al . 2002) and in many of our previous studies (Ullrich et al .…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the ELISA data on active TGF-b, mink lung epithelial cell (Mv1Lu, ATCC, Manassas, VA) proliferation assays were employed. The effects of fibroblast cell culture supernatants or titrated dilutions of rhTGF-b on 3 H-thymidine incorporation were tested with and without neutralizing anti-pan-TGF-b antibody (clone 1D11 from R&D Systems), following the standard protocol (Ghahary et al, 2002). Before testing, the fibroblast cell culture supernatants were cleared of cellular debris by centrifugation, to avoid possible cell membrane-dependent activation of TGF-b (Ghahary et al, 2002).…”
Section: Collagen Production Assaysmentioning
confidence: 99%